Liminality and Critical Event Studies
XVIII, 299 p. 9 illus.
Keywords: This book explores and challenges the concept and experience of liminality as applied to critical perspectives in the study of events. It will be of interest to researchers in event studies, social and discursive psychology, cultural and political sociology, and social movement studies. In addition, it will provide interested general readers with new ways of thinking and reflecting on events. Contributing authors undertake a discussion of the borders, boundaries, and areas of contestation between the established social anthropological concept of liminality and the emerging field of critical event studies. By drawing these two perspectives closer together, the collection considers tensions and resonances between them, and uses those connections to enhance our understanding of both cultural and sporting events and offer fresh insight into events of activism, protest, and dissent. Dr. Ian R. Lamond is a Senior Lecturer at Leeds Beckett University (UK). His work focuses on critical approaches to understanding events. His interests include events of protest and dissent, the eventalisation of the political, the commodification of death, cult fiction fandom, and graphic storytelling. His other works include two edited collections and two co-authored monographs. Dr. Jonathan Moss is a Senior Lecturer at Leeds Beckett University (UK). His PhD dissertation used phenomenological psychology to situate music festival experiences in the ideographic Lifeworld of the attendees. He is currently writing two papers: one regarding the use of descriptive experience sampling methods in event studies, and the other considering how neurophenomenology contributes to our understanding of collective and shared emotions.